2002
DOI: 10.1021/ja026296l
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Heck-Type Reaction of Alkyl Halides with Styrenes

Abstract: A cobalt complex, CoCl2[1,6-bis(diphenylphosphino)hexane], catalyzes an alkylation reaction of styrenes in the presence of Me3SiCH2MgCl in ether to yield beta-alkylstyrenes. A variety of alkyl halides including alkyl chlorides can be employed as an alkyl source. A radical mechanism is strongly suggested for this alkylation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(76 citation statements)
references
References 12 publications
2
70
0
4
Order By: Relevance
“…This system can allow the introduction of a carbon moiety carrying an ester group (run 9). Under the same conditions, CH 2 ¼ CHMgBr, PhB(OH) 2 , and PhC ¼ CSn(n-Bu) 3 were ineffective.…”
Section: ð1þmentioning
confidence: 97%
See 1 more Smart Citation
“…This system can allow the introduction of a carbon moiety carrying an ester group (run 9). Under the same conditions, CH 2 ¼ CHMgBr, PhB(OH) 2 , and PhC ¼ CSn(n-Bu) 3 were ineffective.…”
Section: ð1þmentioning
confidence: 97%
“…Competitive reactions of a mixture of primary, secondary, and tertiary alkyl bromides showed that the reactivities of the halides increase in the order primary < secondary < tertiary. A possible reaction pathway involving single electron transfer from a nickelate complex to alkyl halides is proposed.Keywords: alkyl halides; butadiene; C À C bond formation; cross-coupling; Grignard reagents; multicomponent reactions; nickelThe transition metal catalyzed coupling reaction of organic halides with organometallic reagents or alkenes has been extensively studied and employed in wide areas of organic synthesis.[1] These types of reactions are initiated generally by the oxidative addition of halides to low-valent metals such as Ni 0 and Pd 0 and the scope of the halides as substrates has been limited to aryl, vinyl, allyl, and benzyl halides, [2,3] partly, due to the slow oxidative addition of alkyl halides to metal complexes. Facile b-elimination from the alkylmetal intermediates also restricted the application of alkyl halides.…”
mentioning
confidence: 99%
“…Oshimas Gruppe entwickelte eine cobaltkatalysierte Variante, bei der sekundäre Alkylbromide mit Styrolderivaten gekuppelt werden. [49] Hierzu sind der Einsatz von 1,6-Bis(diphenylphosphanyl)hexan (dpph) als Ligand sowie ein Überschuss an Alkylhalogenid (1.5 ¾quiv) erforderlich. Die Zugabe von Trimethylsilylmethylmagnesiumbromid ist notwendig, jedoch wird dieses nicht ins Produkt eingebaut (Schema 26).…”
Section: Heck-reaktionen Mit Organometallnucleophilenunclassified
“…236 Articles describing, or of relevance to, catalytic reactions of group 9 metals that have not been mentioned above include the detection by in situ IR spectroscopy of the 'missing link' [HRh(CO) 4 ] for the first time, 4 the use of parahydrogen for the detection of rhodium and iridium species present in very low concentration during hydroformylation of alkenes, 237,238 the nature and roles of catalytic promoters in late metal carbonylation reactions, 239 and a DFT study of cobalt-mediated alkene polymerisation which detects an inverse isotope effect due to a β-agostic interaction in the resting state of the catalyst [Cp*Co(Et)(P(OMe) 3 )] ϩ . 240 Important alkyl coupling reactions have also been investigated including cobalt-catalysed Heck-type reactions between alkyl halides and styrene 241 and alkyl halides and allylic Grignard reagents. 242 The direct observation and mechanism of aldehyde insertion into rhodium() aryl and alkoxide complexes has also been reported and intermediates characterised.…”
Section: Cobalt Rhodium Iridiummentioning
confidence: 99%